2014
DOI: 10.1021/ct5002279
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the All-α to All-β Conformational Transition of RfaH-CTD: Molecular Dynamics Simulation and Markov State Model

Abstract: The C-terminal domain of the bacterial transcription antiterminator RfaH undergoes a dramatic all-α-helix to all-β-barrel transition when released from its N-terminal domain. These two distinct folding patterns correspond to different functions: the all-α state acts as an essential regulator of transcription to ensure RNA polymerase binding, whereas the all-β state operates as an activator of translation by interacting with the ribosomal protein S10 and recruits ribosomal mRNA. Accordingly, this drastic confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
65
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 43 publications
17
65
2
Order By: Relevance
“…This is supported by previous observations that disruption of the E48:R138 salt bridge located in this region led RfaH to exist in equilibrium between the autoinhibited and active folds (12). However, this view contrasts with conclusions drawn from other computational approaches (18,22), which suggested that contacts involving RfaH CTD residues comprising the strand β 3 are particularly stable and nucleate the β-barrel, as solution dynamics do not display high stability in this region for RfaH or NusG CTD in the β-fold (Fig. S3).…”
Section: Figuresupporting
confidence: 63%
See 2 more Smart Citations
“…This is supported by previous observations that disruption of the E48:R138 salt bridge located in this region led RfaH to exist in equilibrium between the autoinhibited and active folds (12). However, this view contrasts with conclusions drawn from other computational approaches (18,22), which suggested that contacts involving RfaH CTD residues comprising the strand β 3 are particularly stable and nucleate the β-barrel, as solution dynamics do not display high stability in this region for RfaH or NusG CTD in the β-fold (Fig. S3).…”
Section: Figuresupporting
confidence: 63%
“…Since the trigger for RfaH metamorphosis is the complete ops-paused TEC (13,14,16), it is challenging to study this process experimentally. Instead, most of the thermodynamic and kinetic studies have used computational approaches to directly explore this fold-switch by simulating either the isolated CTD (18)(19)(20) or the entire RfaH protein (21,22). Although the RfaH CTD is composed of only 51 residues (residues 112-162), its transition from alpha to beta has not been observed through conventional molecular dynamics (19), but through the use of enhanced sampling techniques (18,20,22) or reduced system granularity (21,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, MSMs have been used to model the folding of proteins to a known native state 50 , or to demonstrate activation pathways and metastable intermediates between known active and inactive structures 5154 . This study expands upon this body of knowledge by presenting a system in which the structure of the active state is experimentally inaccessible, and these MSMs resolve the active state through simulation alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, probing such fold switching and mapping their energy landscape by experiments or in silico is a challenge. [10][11][12][13][14] Computationally, the problem is that the exploration of the ensemble of possible structures and the conversion between these structures happens on timescales that, on general-purpose computers, are not accessible in all-atom molecular dynamics simulations with explicit solvent. Enhanced sampling techniques such as Replica Exchange Molecular Dynamics (REMD) [15][16][17][18][19][20] promise to overcome this problem by realizing a random walk in temperature which allows the system to escape out of traps and cross barriers by explorations to higher temperatures.…”
Section: Introductionmentioning
confidence: 99%